2022
DOI: 10.1364/ao.474920
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency enhancement of ultrathin CIGS solar cells by optimal bandgap grading. Part II: finite-difference algorithm and double-layer antireflection coatings

Abstract: In Part I [Appl. Opt. 58, 6067 (2019)APOPAI003-693510.1364/AO.58.006067], we used a coupled optoelectronic model to optimize a thin-film C u I n 1 − ξ G a ξ S e 2 (CIGS) solar cell with a graded-bandgap photon-absorbing layer and a periodically corrugated backreflector. The increase in efficiency d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…(16) conforms to the experimental data reasonably well without using surface defects, 69 so all performance parameters of CIGS thin-film PVSCs can be predicted using only the bulk material-response parameters. Equation (16) helps model the defect density in graded-bandgap CIGS solar cells 69 and can be expected to do the same for quantum-well-based CIGS solar cells, 50 thereby assisting experimentalists.…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…(16) conforms to the experimental data reasonably well without using surface defects, 69 so all performance parameters of CIGS thin-film PVSCs can be predicted using only the bulk material-response parameters. Equation (16) helps model the defect density in graded-bandgap CIGS solar cells 69 and can be expected to do the same for quantum-well-based CIGS solar cells, 50 thereby assisting experimentalists.…”
Section: Resultssupporting
confidence: 69%
“…As our focus is on modeling the electrical characteristics of the solar cell, not on how it interfaces with an external circuit, both terminals were assumed to be ideal ohmic contacts. We used a one-dimensional drift-diffusion model 33 , 34 , 68 , 69 to investigate the transport of electrons and holes for z[Lnormalw,Lnormald]. The solution of the drift-diffusion system yields the electron current density Jnormaln(z), the hole current density Jnormalp(z), and the device current density Jdev=Jn(z)+Jp(z),z[Lw,Ld],which is independent of z but is a function of the voltage Vext applied across the planes z=Lnormalw and z=Lnormald.…”
Section: Optoelectronic Simulationmentioning
confidence: 99%
“…The schematic of a standard MgF 2 /AZO/od-ZnO/CdS/CIGS/Al 2 O 3 /Mo thin-film solar cell is shown in figure 2(a) [18]. The solar cell is homogeneous in any xy plane, the z axis of the Cartesian coordinate system being aligned parallel to the thickness direction.…”
Section: Optoelectronic Simulation 21 Solar-cell Descriptionmentioning
confidence: 99%
“…A recent theoretical investigation demonstrated that judiciously selected compositional-grading profiles (i.e. ξ as a function of z) leading to bandgap grading [18] in the CIGS photon-absorbing layer can enhance the efficiency. Furthermore, it has been experimentally observed that, despite the induction of higher defect density by significant compositional grading in the CIGS layer, there is a concurrent reduction in open-circuit voltage loss.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation